PERSONALIZED LEARNING IN SECONDARY EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Duisekeyeva, Б.; Koneva, С.; Sarsembayeva, Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The development of 21st-century skills represents one of the most significant global challenges in modern education. It focuses on bridging the gap between the achievements of secondary education and the requirements of higher education institutions, as well as addressing the needs of employers and students. According to the vision of Kazakhstan's 2023–2029 education reform, the educational process is oriented toward students and their individual needs.This article examines the impact of personalized learning and artificial intelligence on the educational process. The challenge of ensuring the successful functioning of an educational trajectory tailored to a student’s potential, personal interests, and needs is addressed through the transition to personalized learning. This approach enhances the quality of knowledge by transforming the roles and actions of both students and teachers. In the digital age, personalized learning has emerged as a strategy attracting the attention of the educational community. It serves as an effective tool for meeting diverse student needs, strengthening engagement, and improving academic performance. The aim of this article is to provide a systematic literature review of personalized learning trends and the impact of artificial intelligence, highlighting key studies, methodologies, advantages, and challenges of personalized education. The research objectives include analyzing major studies on personalized education and identifying its benefits and drawbacks. The PRISMA methodology was employed for the systematic literature review, covering articles from 2014 to 2023 in the Scopus database. The article explores various aspects of the development of personalized learning methodologies, such as MOOCs, intelligent mentoring systems, online and adaptive systems, augmented reality, and virtual reality. The findings of the study can be used to develop project-based systems for implementing personalized learning in educational institutions.